2018
DOI: 10.2147/opth.s156497
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid wide-angle viewing-endoscopic vitrectomy using a 3D visualization system

Abstract: PurposeTo introduce a hybrid wide-angle viewing-endoscopic vitrectomy, which we have reported, using a 3D visualization system developed recently.Subjects and methodsWe report a single center, retrospective, consecutive surgical case series of 113 eyes that underwent 25 G vitrectomy (rhegmatogenous retinal detachment or proliferative vitreoretinopathy, 49 eyes; epiretinal membrane, 18 eyes; proliferative diabetic retinopathy, 17 eyes; vitreous opacity or vitreous hemorrhage, 11 eyes; macular hole, 11 eyes; vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…49 A recent report describes the successful hybridization of ocular endoscopy with a 3D visualization system to manage vitreoretinal disease. 50 Despite clearly defined advantages, ocular endoscopy utilization remains low in part due to the ergonomic challenges of multiscreen off-axis viewing away from the main surgical field. DAVS based same screen simultaneous viewing of endoscopy video alongside the 3DHD surgical field video reduces these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…49 A recent report describes the successful hybridization of ocular endoscopy with a 3D visualization system to manage vitreoretinal disease. 50 Despite clearly defined advantages, ocular endoscopy utilization remains low in part due to the ergonomic challenges of multiscreen off-axis viewing away from the main surgical field. DAVS based same screen simultaneous viewing of endoscopy video alongside the 3DHD surgical field video reduces these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, use of an endoscope makes it possible to observe the peripheral area of the fundus without any scleral indentation 14. Combining the use of a wide-angle viewing system and an endoscope as a visualization tool for each step of the surgery is referred to as “hybrid vitrectomy”, with the end result of a much more efficient procedure 5,6…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on the efficacy of an ocular endoscope14 and on the combined use of a wide-angle viewing system and an endoscope, which we call “hybrid vitrectomy” 5,6. However, since an ocular endoscope can only provide a two-dimensional (2D) view, it is necessary to create an empirical stereoscopic vision during the endoscopy.
Figure 1The wide-angle viewing image is integrated on the large NGENUITY 3D monitor (right) that is placed at the foot of the surgical bed.
…”
Section: Introductionmentioning
confidence: 99%
“…Its rst use in cataract surgery was reported by Weinstock in 2008, while Riemann stated that 3D system was introduced in vitrectomy world starting from 2010. 3D heads up surgery not only display a better image with manipulation of colour and brightness of images, but it also enables access to multiple images at the same time such as images of the optical coherence tomography (OCT) and endoscopic view [10]. 3D visualization in OCT and its implementation in vitreoretinal surgeries resulted in higher success rate [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective surgical case series involving 113 of vitrectomies and 90 phacoemulsi cations revealed that none of these cases converted from the 3D surgery to the traditional ophthalmic surgery [10].…”
Section: Introductionmentioning
confidence: 99%